Sociology in focus AQA AS level - Haralambos, Michael; Langley, Peter, 1954- ([Ormskirk?] : [Causeway], 2008)
This new edition provides a perfect match to AQA's new GCE specification. It offers students a complete solution to achieving success at GCE with the most accessible resources available for the most popular options.
Previous ed.: 2003.
Includes bibliographical references (p. 217-222) and index.
Keywords: Sociology -- Examinations -- Study guides; Society